Direct profiling of breast cancer-derived extracellular vesicles using Pd-perovskite electrochemical biosensing platform - Dezhakam, Ehsan; Khalilzadeh, Balal; Naseri, Abdolhossein; Rahbarghazi, Reza; Mahmoudi, Elham; Niaei, Aligholi; Mahdipour, Mahdi; Mardi, Narges; Isildak, Ibrahim (SPRINGER WIEN, 2024)
Extracellular vesicles (EVs) harbor several signaling molecules to maintain intercellular communication. Based on the exosomal cargo type, metabolic, genomic, and proteomic status of parent cells can be investigated. Due to the existence of trivial levels of target molecules inside EVs, the application of accurate and sensitive detection methods is mandatory. Here, we used an electrochemical immunosensor using a biotinylated monoclonal CD63 antibody as the capturing element for the detection of EVs isolated from MDA-MB-231 cells and cancer patients. Simultaneously, breast cancer biomarker CA-15-3 was detected in isolated EVs using a sandwich method to increase specificity. Data indicated a linear dynamic range of 2000-10000 EVs/mu L and a lower limit of quantification of 2000 EVs/mu L. Based on data from real sample analysis, the levels of exosomal CA-15-3 can differ according to the severity and systemic content of this factor. Pd-perovskite-based immunosensor provides a platform for quick and in-depth analysis of EVs isolated for cancer cells.
Keywords: Breast cancer; Extracellular vesicles; Perovskite; Electrochemical; Biosensing; NONENZYMATIC GLUCOSE SENSOR; EXOSOMES; CEA; NANOPARTICLES; STATISTICS; METASTASES; DIAGNOSIS; DISEASE; CO; Oncology; Science & Technology - Other Topics